PENDAMPINGAN PASAR MODAL PADA SISWA SMKN 2 KEDIRI - Novie Astuti Setianingsih; Atik Tri Andari; Wiwiek Kusumaningasmoro; Eti Putranti; Elmi Rakhma Aalin (JPM PAMBUDI, 2019)
The purpose of the implementation of community service activities is to prepare SMKN 2 Kediri students and millennials to better understand and master the Capital Market. The method of implementation uses the experiential learning method, which is a learning method from experience. The method used is the lecture method, the question and answer method and the simulation method. For simulation method by doing multiple choice questions, crossword simulation (TTS), kotak katik simulation, case debate simulation and stock treading simulation in Indonesia stock exchange using Reliance Securities and MNC Securities. The implementation of Community Service was held on October 1, 2019 until October 14, 2019 for a period of 10 days attended by 22 participants and carried out at the Indonesia Stock Exchange Politeknik Negeri Malang PSDKU Kediri.